IMMUNOHISTOCHEMICAL FEATURES OF CYTOKERATINS AND CARCINOEMBRYONAL ANTIGEN EXPRESSION IN GASTRIC INTESTINAL METAPLASIA - Vernygorodskyi, S.V. (World of Medicine and Biology, 2012)
The features of cytokeratins and carcinoembryonal antigen expression in gastric intestinal metaplasia was studied on the basis of immunohistochemical analysis. A positive expression of СК7 and CEA in areas of intestinal metaplasia are evidence of its immature, incomplete or gastrointestinal phenotype, but expression of СК20 is more distinctive for complete, mature/solely small-intestinal phenotype of gastric intestinal metaplasia.